Gender Mainstreaming in Natural Disaster Management: Study of Planning for Strengthening Women's Capacity Against Disasters in Bantul District - Ramailis, Nurfadni; Sakir, Sakir (Amalee: Indonesian Journal of Community Research and Engagement, 2024)
Planning to strengthen women's capacity to deal with disasters in Bantul Regency is one of the main factors in this research. Because women are ultimately categorized as a vulnerable group, this vulnerability is caused by women's lack of knowledge about disasters. This research aims to analyze plans to strengthen women's capacity to deal with natural disasters in Bantul Regency. This research uses Participatory Rural Appraisal (PRA) methods supported by primary and secondary data using Vos Viewer analysis. Secondary data documents the activities provided by BPBD for women's groups. This research uses data analysis techniques with data reduction, presentation, and conclusion. This research also shows that there are positive steps provided by BPBD to women's groups so that they can participate in strengthening women's capacity to face disasters. Based on research findings, the Bantul Regency Regional Disaster Management Agency (BPBD) plans to strengthen women's capacity to deal with disasters by providing socialization about disasters and disaster simulations to women's groups.